Interjoint coordination in kicking a moving target: A comparison between elite and nonelite taekwondo players - Straiotto, B. G.; Cook, D. P.; James, D. C.; Seeley, P. J. (Journal of Applied Biomechanics, 2021)
Patterns of interjoint coordination in the kicking legs of taekwondo players were investigated to understand movement pattern variability as a functional property of skill level. Elite and nonelite players performed roundhouse kicks against a custom-built moving target fitted with an accelerometer, and movements were recorded by motion capture. Average foot segment velocities of 13.6 and 11.4 m/s were recorded for elite and nonelite players, respectively (P < .05), corresponding to target accelerations of 87.5 and 70.8g (P < .05). Gradient values derived from piecewise linear regression of continuous relative phase curves established the comparative incoordination of nonelite taekwondo players in the form of an overshoot behavior during the crucial period leading to target impact (P < .05). This overshoot was apparent in both knee-hip and ankle-knee continuous relative phase curves. Elite players generated greater limb speed and impact force through more effective limb segment coordination. The combination of continuous relative phase and piecewise linear regression techniques allowed identification of alternate joint control approaches in the 2 groups.